Stability and Functional Outcome of ACL Reconstruction Using Semitendinosus Autograft: A Prospective Study of 20 Patients - Akhtar Zaman, Javed Iqbal Khan, Zeshan Mustafa, Sajjad Ahmed, Raziullah, Afzal Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anterior cruciate ligament (ACL) reconstruction is one of the most frequently performed procedures in young, active patients. Graft selection remains debated, with hamstring autografts increasingly preferred due to reduced donor-site morbidity. Objective: To evaluate stability, functional outcomes, and predictors of success in patients undergoing ACL reconstruction using semitendinosus autograft. Methods: Twenty patients underwent arthroscopic ACL reconstruction with quadrupled semitendinosus autograft and were followed for 12 months. Functional outcomes were measured using International Knee Documentation Committee (IKDC) subjective score, Lysholm knee score, and Tegner activity scale. Stability was assessed with Lachman, pivot shift, and KT-1000. Statistical analysis included paired t-tests for continuous outcomes, chi-square for categorical outcomes, and logistic regression to identify predictors of excellent IKDC outcome. Results: At 12 months, mean IKDC improved from 52.6 to 86.3 (p<0.001), Lysholm from 55.8 to 91.5 (p<0.001), and Tegner from 3.1 to 6.8 (p<0.001). Negative Lachman was present in 90% and negative pivot shift in 85% of patients. KT-1000 revealed side-to-side difference ≤3 mm in 90% of patients. Complications included transient stiffness (10%) and hamstring weakness (15%). Logistic regression showed age <30 years and sports-related injury were significant predictors of excellent IKDC outcome (p<0.05). Conclusion: Semitendinosus autograft is an effective graft choice for ACL reconstruction, providing reliable stability, excellent functional recovery, and minimal donor-site morbidity. Younger age and sports-related injuries were associated with superior outcomes. Keywords: ACL reconstruction; semitendinosus graft; hamstring autograft; functional outcome; logistic regression